The Influence of Capital, Education, and Motivation of Female Fisherwomen on the Development of Fisheries Entrepreneurship in Manado City - Sandra Ingried Asaloei; Welson Yappi Rompas; Juliana W. Tumiwa (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Female fisherwomen in coastal Indonesia play a key role in post-harvest fisheries activities, yet their entrepreneurship development remains constrained by limited capital access, inadequate education, and motivational barriers. Objective: This study examines the influence of capital access, educational level, and entrepreneurial motivation on fisheries entrepreneurship development among female fisherwomen in Manado City, using an Islamic entrepreneurship framework. Method: A quantitative survey design was employed with 120 respondents selected through purposive sampling across four coastal sub-districts of Manado. Multiple linear regression was used to test four hypotheses. Results: Capital access (β = 0.312, p < 0.01), educational level (β = 0.287, p < 0.01), and entrepreneurial motivation (β = 0.341, p < 0.01) each significantly and positively influence fisheries entrepreneurship development, with the model explaining 60.8% of variance (Adj. R² = 0.608). Entrepreneurial motivation is the strongest predictor. Conclusion: Integrating Islamic microfinance instruments (qard hasan, mudharabah) alongside gender-responsive entrepreneurship education and productive waqf mechanisms can meaningfully strengthen women's fisheries entrepreneurship in coastal Indonesia.